Structural and active site modification studies implicate Glu, Trp and Arg in the activity of xylanase from alkalophilic Bacillus sp (NCL 87-6-10) - Balakrishnan, H.; Satyanarayana, L.; Gaikwad, S. M.; Suresh, C. G. (Enzyme and Microbial Technology, 2006)
Structural studies and residue modification using group specific reagents were used to ascertain the role of different functional groups in xylanase from alkalophilic Bacillus sp. (NCL 87-6-10). Treatment with N-bromosuccinimide resulted in fast enzyme inactivation. Reaction with Woodward's reagent K resulted in initial fast followed by slower inactivation. In both cases enzyme was protected against inactivation by the substrate, xylan. The reaction of the enzyme with phenylglyoxal has revealed one essential arginine residue at the active site. The three-dimensional structural analysis of the xylanase at 2.8 angstrom resolution also implicates involvement of Trp, and Arg residues and carboxylate groups in the binding of substrate and in the catalysis of xylanase. (c) 2005 Published by Elsevier Inc.
Keywords: active-site residues; alkaline xylanase; Chemical modification; three-dimensional structure